Half-life extension technologies for haemostatic agents - Mannuccio, Pier Mannucci (Thrombosis and Haemostasis, 2015)
The use of plasma-derived and recombinant coagulation factors for the treatment of haemophilia A and B is well established and permits patients to live a relatively normal life. In order to improve treatment options, several products are in development, which have a prolonged duration of action, thus enabling less frequent prophylactic dosing and aiming to reduce the burden of treatment. Several innovative approaches are being pursued to extend the half-life of factor VIIa, factor VIII and factor IX, utilising technologies such as Fc fusion, recombinant albumin fusion and addition of polyethyleneglycol (PEG) (PEG ylation). These methods prolong the time in the circulation by reducing degradation and elimination. This review summarises the technologies and products in development and their stages of development, and also discusses their pros and cons.
Keywords: Haemophilia; prolonged half-life; coagulation factors